Early, Prophylactic Thyroidectomy in Hereditary Medullary Thyroid Carcinoma: A 26-year Monoinstitutional Experience. (October 2015) - Pelizzo, Maria R.; Torresan, Francesca; Boschin, Isabella M.; Nacamulli, Davide; Pennelli, Gianmaria; Barollo, Susi; Rubello, Domenico; Mian, Caterina
Abstract : Purpose: Prophylactic thyroidectomy has been encouraged for children with REarranged during Transfection (RET) germline mutations to prevent the onset, persistence, or recurrence of medullary thyroid carcinoma (MTC). The American Thyroid Association (ATA) recently published guidelines on the timing of prophylactic thyroidectomy. Our aim here was to seek information on the optimal timing of surgery for carriers of RET gene mutations with no clinical evidence of disease, bearing in mind the ATA recommendations. Methods: From 1986 to 2012, total thyroidectomy was performed at our institute on 31 carriers of RET gene mutations, 28 of them found on family screening in the post-RET era, and the other 3 under 20 years of age and classified as "early cases" in the pre-RET era. The following parameters were studied: age at surgery, MTC risk, basal calcitonin (bCT) and pentagastrin-stimulated calcitonin (sCT), surgery outcomes, and persistence of disease. Results: By family, the most prevalent mutation was codon 634 (30%) RET mutation. The youngest MTC patient was 5 years old. Overall, MTC was found in 68% of cases; 52% of the sample had a normal bCT and 25% had an sCT unresponsive to pentagastrin. The only factor predicting the risk of MTC at final histology was an ATA-RET risk level C. On receiver oparating curves analysis, a cutoff at age over 24 years predicted ( P =0.06) a yield of MTC in the resected specimen. Interestingly, none of the patients with MTC had nodal involvement (0/21 patients with MTC). Yet, none of the patients had permanent nerve palsy, and only 1 patient had permanent hypocalcemia. bCT was normal postoperatively and during the follow-up in all but 3 patients. Conclusions: It is noteworthy that the yield of cancer in removed thyroid was 100% for codon 634 (9/9 patients, 5 families) and for codons 891 and 768 (2/2 patients in each of the 2 families with those codon mutations), followed by 67% for codon 609 (4/6 patients, 1 family), and 60% for codon 618 (3/5 patients in 4 families) RET mutation. In cases of ATA-RET levels B and C, waiting for an increase in bCT and/or sCT may not guarantee that prophylactic surgery is performed before MTC develops (which would assure patients a life free of diseases and a less-invasive surgical procedure, without any need for central lymph-node dissection).